Dampak Cloud Accounting dan Fintech Terhadap Peran Akuntan Dimoderasi Etika Akuntansi - Ni Putu Agustin Prastika Dewi; Putu Putri Prawitasari (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to analyze the influence of cloud accounting and financial technology (fintech) on the role of accountants, with accounting ethics as a moderating variable. A quantitative approach was employed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The research sample consisted of 120 respondents, namely internal accountants of companies in Denpasar City who utilize cloud accounting and fintech systems in their accounting and financial reporting activities. he study found that cloud accounting (β = 0.318, t = 3.472, p = 0.000) and fintech (β = 0.377, t = 4.225, p = 0.000) both have a positive and significant impact on the role of accountants, indicating that technological advancement strengthens accountants’ professional functions. However, accounting ethics did not significantly moderate either relationship (p > 0.05), suggesting that in the digital era, the enhancement of accountants’ roles is driven more by technological adaptability and competence than by ethical moderation. Overall, this study emphasizes that digital transformation through cloud accounting and fintech drives the evolution of the accountant’s role from an administrative function toward a strategic, data-driven decision-making function.